Data availability and participatory approach: the right mix for enhancing Mediterranean fisheries’ sustainability - Malvarosa, Loretta; Basilone, Gualtiero; Carbonara, Pierluigi; Carpentieri, Paolo; Cozzolino, Maria; Follesa, Maria Cristina; Gambino, Monica; Gancitano, Vita; Parreno Duque, David; Pesci, Paola; Vielmini, Ilaria; Scarcella, Giuseppe (Frontiers in Marine Science, 2023)
A misalignment between the legislation and the effectiveness of Mediterranean fisheries management has emerged due to the status of the stocks (still largely in overfishing) and the discontent of stakeholders regarding management plans and tools that are not always recognized as appropriate to the characteristics of the concerned fisheries. Stakeholders’ involvement in management processes is one of the main pillars of the Common Fisheries Policy revision. The literature underlines, in an increasingly urgent manner, the importance of stakeholders fully understanding the contents of management plans and, vice versa, necessary for the successful implementation of policies. Focusing on the path towards sustainability endorsed by the BluFish project, the paper tries to provide an answer about the sustainability of some selected Southern Italian fisheries, by adopting the assessment approach of the Marine Stewardship Council. The assessment approach, based on a set of Performance Indicators and on a well-defined scoring scheme, focuses on three dimensions of sustainability. In addition to the classic assessment of the state of the stocks, there is an extensive screening of the impact of anthropic activity such as fishing on the entire ecosystem, including both the impact on accessory species and on vulnerable habitats and species. The evaluation adopted goes even further, with an approach that also includes the management and governance sphere, also trying to evaluate the level of involvement of the operators in the decision-making process. The paper illustrates that the selected fisheries are not fully sustainable but some of them have excellent potential for improvement even in the short term by identifying and implementing the appropriate action. The most relevant weaknesses identified refer to the low scores obtained for sustainability of stocks, mainly around the Harvest Control Rules (HCR) and the Harvest Strategy indicators, highlighting the importance of improving the management of the assessed stocks. The paper highlights how data and scientific knowledge availability is essential for a detailed mapping and evaluation of fishing activities but also that the path towards more sustainable and responsible fisheries does not work without a strong participation of all the key stakeholders.